Предмет: Математика,
автор: Onlyangelshavewings
-12а-25b+18а+14b =
b-(b+6)+(b-18) =
-7(m-4)+5(m+2) =
с развёрнутым ответом
Ответы
Автор ответа:
1
Пошаговое объяснение:
-12а-25b+18а+14b = (18а-12а)+(14b-25b) = 6a+(-11b) = 6a-11b
b-(b+6)+(b-18) = b-b-6+b-18 = b-24
-7(m-4)+5(m+2) = -7m+28+5m+10 = (28+10)+(5m-7m) = 38+(-2m) = 38 -2m
Похожие вопросы
Предмет: Русский язык,
автор: zxcvbnmlkjhgfdsadcf
Предмет: Қазақ тiлi,
автор: в0а0л0е0р0и0я0
Предмет: Русский язык,
автор: Аноним
Предмет: Литература,
автор: taekookarmy
Предмет: Английский язык,
автор: 68Саша68